Katalin Juhász (1952-2012) - editors, The (Teaching Mathematics and Computer Science, 2013)
Katalin Juhász was born in 1952, in Tarnaméra (Hungary), where she also completed her primary school studies. She finished Erzsébet Szilágyi Highschool, Eger, in 1971 and she graduated in mathematics from Lajos Kossuth University (KLTE), Debrecen, in 1976. That year she married a physicist and together they brought up their son.